Intramedullary nailing of open tibia and femur fractures through the supra & infrapatellar approach. Is septic arthritis a real concern? - Armas, Selma (Division of General Surgery, 2025)
Background: A theoretical risk exists concerning the development of septic arthritis in the knee following the utilisation of intramedullary nailing techniques. These techniques encompass the supra/infrapatellar approach during tibial nailing and the retrograde approach during femoral nailing. This potential risk stems from the mechanical bridging of the knee joint in both methodologies. The susceptibility to this risk increases notably in cases involving open fractures, as all associated wounds are deemed contaminated. Consequently, the potential introduction of infection into the knee joint consistently remains a concern for the surgeon performing these procedures. Methods: All instances of open fractures involving the tibia and femur, categorised according to the Gustillo Anderson classification as grades 1 through 3C, within the timeframe spanning from January 2017 to December 2018, were identified. Inclusion criteria encompassed cases where fracture fixation was accomplished utilising the retrograde femur intramedullary nail (IMN) approach and the suprapatellar approach for tibial fractures. Recorded cases underwent a comprehensive 12-month follow-up period, during which clinical evaluation for evidence of union and any indications of infection at both the surgical and fracture wound sites (FRI) was conducted. Findings: The study included a total of 116 open fracture cases that met the inclusion criteria, comprising 34 cases of femur fractures and 82 cases of tibia fractures. No instances of septic knee arthritis were detected within this cohort. Conclusion: Within both the femur and tibia open fracture groups subjected to treatment involving the use of intramedullary nails via a through-the-knee surgical approach, the study found no reported septic knee arthritis cases. Revealing that septic arthritis of the knee post retrograde femur nailing and/or suprapatellar tibia nail fixation may not be a real concern.